Quaternary ammonium compounds in roots and leaves of Capparis spinosa L. from Saudi Arabia and Italy: investigation by HPLC-MS and 1H NMR. Issue 9 (3rd May 2019) - Al-Tamimi, Amal; Khatib, Mohamad; Pieraccini, Giuseppe; Mulinacci, Nadia
Abstract: Capparis spinosa L. is a perennial plant typical of the Mediterranean flora and a multipurpose plant used for curing various human ailments. Quaternary ammonium compounds (QACs), as constituents of Capparaceae, play important roles in protecting against abiotic stress. Aim of this work was to determine QACs in root and leaves of caper from two proveniences. The presence of stachydrine, choline, glycine betaine and homo-stachydrine has been confirmed by high resolution MS, while 1 H NMR was applied to quantify the main QACs in the aqueous extracts. Stachydrine was quantified at 20.2 mg/g and 32.3 mg/g on dry leaves from South of Italy and Saudi Arabia, respectively, while a minor content was in dry roots (from 10.4 to 12.5 mg/g). Choline was considerably lower both in leaves and roots (from 0.3 to 1.2 mg/g). To our knowledge, this is the first report on the determination of QACs both in root and leaves of C. spinosa . Abstract :